Evaluating tobacco retailer experience and compliance with a flavoured tobacco product restriction in Boston, Massachusetts: impact on product availability, advertisement and consumer demand. Issue Volume 29:Issue e1(2020) (14th October 2019) - Kephart, Lindsay; Setodji, Claude; Pane, Joseph; Shadel, William; Song, Glory; Robertson, Jennifer; Harding, Nikysha; Henley, Patricia; Ursprung, Wannakuwatte Waduge Sanouri
Abstract : Background: Flavoured tobacco products are widely available in youth-accessible retailers and are associated with increased youth initiation and use. The city of Boston, Massachusetts restricted the sale of flavoured tobacco products, including cigars, smokeless tobacco and e-cigarettes, to adult-only retailers. This paper describes the impact of the restriction on product availability, advertisement and consumer demand. Methods: Between January and December 2016, data were collected in 488 retailers in Boston at baseline and 469 retailers at 8-month follow-up, measuring the type, brand and flavour of tobacco products being sold. Process measures detailing the educational enforcement process, and retailer experience were also captured. McNemar tests and t-tests were used to assess the impact of the restriction on product availability. Results: After policy implementation, only 14.4% of youth-accessible retailers sold flavoured products compared with 100% of retailers at baseline (p<0.001). Flavoured tobacco product advertisements decreased from being present at 58.9% of retailers to 28.0% at follow-up (p<0.001). Postimplementation, retailers sold fewer total flavoured products, with remaining products often considered as concept flavours (eg, jazz, blue). At follow-up, 64.0% of retailers reported that customers only asked for flavoured products a few times a week or did not ask at all. Retailers reported that educational visits and the flavoured product guidance list aided with compliance. Conclusion: Tobacco retailers across Boston were largely in compliance with the regulation. Availability of flavoured tobacco products in youth-accessible retailers declined city-wide after policy implementation. Strong educational and enforcement infrastructure may greatly enhance retailer compliance.